Development of nanofiber based immunosorbent surface for the removal of fluoxetine from breast milk - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN; AKBAY, TUĞBA (TAYLOR & FRANCIS AS, 2019)
In this study, novel bioactive material has been identified for the removal of fluoxetine from breast milk. For this purpose, the poly (vinyl alcohol)/poly (acrylic acid) based nanofiber with an antibody immobilized has been developed. The efficiency of this nanofiber was compared with the control pore glass (CPG) either in milk. The bioactive nanofiber removed fluoxetine significantly higher than the CPG. The efficiency of the fluoxetine removal with the nanofiber was 98% in breast milk. In conclusion, the nanofiber based immunosorbent surface that is developed in this study was found to be efficient for chemical sensing of fluoxetine. [GRAPHICS] .
Keywords: Electrospinning; nanofiber; immobilization; fluoxetine; breast milk; POLY(VINYL ALCOHOL); CROSS-LINKING; POSTNATAL DEPRESSION; IMMOBILIZATION; MEMBRANES; POLYMER; FIBERS; DRUG; ANTIBODIES; SCAFFOLDS